The Effect of Scanning Strategies on Geometrical Accuracy & Surface Roughness of H13 Tool Steel Parts in Laser Powder Bed Fusion Process - Ashok Kumar, Rajendran; Ahmadnia Feizabadi, Masoud (My University, 2019)
Additive Manufacturing (AM) combined with the development of new materials and the current available processes, has the potential to revolutionize the way of manufacturing products. Making parts with higher geometrical precision and better surface finish will pace up this revolution. In this project the effect of scanning strategies on geometrical accuracy and surface roughness of parts made of H13 tool steel via SLM process is investigated. A raster scanning pattern with 3 different hatch rotation angles(10, 67 and 180 degrees) were implemented. The effect of contouring was also studied by comparing the results from contoured and non-contoured samples. The results show that the 10 degree hatch rotation angle causes less deviation even though 67 degree is commonly mentioned as the optimum hatch rotation angle in most of the research papers. The surface roughness in parts printed without the contouring step is of poorer quality than the ones with contouring. Irrespective of employing this contouring step or not, a post-processing step like milling or grinding is required to achieve the desired surface roughness. Therefore, it can be suggested to skip contouring in order to save printing time. However, in terms of achieving the best geometrical accuracy, it is recommended that the contouring step is employed for printing thin wall of 0.5mm thick.
Keywords: SLM, Geometry Assurance, Surface Roughness, Scanning Strategy, Contouring; Hatch Rotation Angle